Education for citizenship: the question posed by social movements (Educação e Pesquisa, 2002)
The article problematizes the relationship between citizenship and the education of the popular classes. It has as its goal to establish a dialogue in space and in time with the concept of citizenship, attempting to verify if the latter concept has contents to contribute to the education of the popular classes, and what are its limits and possibilities that must be made clear in order to give visibility and room to new concepts and practices. To fulfill this goal the concepts of citizenship and education are immersed in history and philosophy or, more specifically, in the conditions for the constitution of a citizen, whose analysis results in the education necessary for such constitution. The contradictions exhibit the possibilities and limits of education as the main road to citizenship, as well as the fact that popular social movements create new forms of producing, living together, and educating themselves. In this process, social movements gestate new concepts whose contents, characterized by practices of cooperation and solidarity, seem to envisage social emancipation in a sense broader than that proposed by the formal principles of freedom and equality upon which the bourgeois citizenship rests. Thus, popular social movements also broaden the horizon of education beyond citizenship.